2021
DOI: 10.3390/jcm10050955
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cardiovascular Risk Scores and Several Markers of Subclinical Atherosclerosis in an Asymptomatic Population

Abstract: Background: The current cardiovascular disease (CVD) primary prevention guidelines prioritize risk stratification by using clinical risk scores. However, subclinical atherosclerosis may rest long term undetected. This study aimed to evaluate multiple subclinical atherosclerosis parameters in relation to several CV risk scores in asymptomatic individuals. Methods: A cross-sectional, single-center study included 120 asymptomatic CVD subjects. Four CVD risk scores were computed: SCORE, Framingham, QRISK, and PROC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
(49 reference statements)
0
17
0
1
Order By: Relevance
“…The risk calculators may integrate CIMT measurement with CV risk factors [ 86 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. The ARIC study published an adjusted FRS calculator incorporating mean-maximum CIMT from six carotid segments and plaque assessment to determine the probability of MI or death from CHD within 10 years [ 96 ].…”
Section: Additive Value Of Cimt and Carotid Plaque To The Traditional Cardiovascular Risk Scoring Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk calculators may integrate CIMT measurement with CV risk factors [ 86 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. The ARIC study published an adjusted FRS calculator incorporating mean-maximum CIMT from six carotid segments and plaque assessment to determine the probability of MI or death from CHD within 10 years [ 96 ].…”
Section: Additive Value Of Cimt and Carotid Plaque To The Traditional Cardiovascular Risk Scoring Systemsmentioning
confidence: 99%
“…Mitu et al found a relationship between CIMT and arterial stiffness with SCORE, FRS, QRISK, and PROCAM in an asymptomatic population [ 100 , 101 ]. The SCORE risk correlated better with CIMT, while the FRS and QRISK seemed more specific for increased arterial stiffness parameters [ 100 ].…”
Section: Additive Value Of Cimt and Carotid Plaque To The Traditional Cardiovascular Risk Scoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAS plays a role in the entire process from the subclinical phase to clinical CVD that is initially insidious until an ischemic accident occurs ( 7 ). Subclinical atherosclerosis is an early indicator of CVD, and identifying asymptomatic individuals is particularly important to reduce the disease burden ( 8 ). Previous studies tended to choose patients with clinical symptoms of atherosclerosis, and few studies focused on asymptomatic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial properties such as vascular stiffness, carotid intima-media complex thickening (CIMT), and plaque formation are important, as non-traditional cardiovascular risk factors associated with risk of fatal and non-fatal cardiovascular events such as myocardial infarction, stroke, and heart failure episodes. Four papers addressed this clinically relevant problem [1][2][3][4].…”
mentioning
confidence: 99%